THE LEGAL PROTECTION OF PEOPLE WITH ASD: AN ANALYSIS OF TOPIC 1082 OF THE STJ AND THE BRAZILIAN LEGAL SYSTEM - Filho, Abrahão Lincoln Sauáia (Seven Editora, 2024)
This article addresses the legal protection of people with Autism Spectrum Disorder (ASD) in Brazil, analyzing Theme 1082 of the Superior Court of Justice (STJ) and its relationship with the Brazilian legal system. Through a literature review and analysis of current legislation, we seek to understand the advances and challenges in the recognition and guarantee of the rights of people with ASD, especially in the context of inclusive public policies and the responsibility of the State to ensure adequate care. Topic 1082 of the STJ, which discusses the mandatory provision of therapies for people with ASD by health plans, is analyzed from the perspective of fundamental rights and the dignity of the human person. The article highlights the relevance of a legal approach that promotes the inclusion, equality, and protection of people with ASD, in accordance with constitutional principles and international regulations ratified by Brazil. DOI:https://doi.org/10.56238/sevened2024.037-047